The Constitution's gift : a constitutional theory for a democratic European Union - Fossum, John Erik (Governance in Europe (London, England), 2011)
This authoritative study considers all aspects of the European Union's distinctive constitution since its inception. A unique political animal, the EU has given rise to important constitutional conundrums and paradoxes that John Erik Fossum and Agustín José Menéndez explore in detail. The authors consider the process of forging the EU's constitution and the set of fundamental norms that define the institutional structure, the decision-making procedures, and the foundations of the Union's democratic legitimacy. Their analysis illuminates the distinctive features of the EU's pluralist constituti.